Pengaruh Model Pembelajaran Sinektik Terhadap Kemampuan Menulis Puisi Peserta Didik Sekolah Dasar - Gea, Wistin Putri; Harefa, Erni Putri Kasih; Zega, Winer Krisyanto; Telaumbanua, Teguh Joiswan; Harefa, Elvin Krisdamaiyanti; Zebua, Meidarman; Zebua, Arisman Kristian; Harefa, Widia Oktafiyani; Harefa, Edward (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This study examines the influence of the synectic learning model on the ability to write poetry of elementary school students. Although writing poetry is recognized as important for improving language skills and creativity, many learners face challenges such as starting to write, choosing the right diction, and staying motivated. To address this problem, this study applies a synectic model that encourages creativity through analogical thinking. Conducted in an elementary school with 58 participants, this quantitative study used SPSS version 25 for data analysis, including validity and reliability tests, as well as classical assumption tests. This study is quantitative research with data collection techniques using questionnaires. Hypothesis testing is carried out by t-test (Partial Test). The results showed that the synectic model significantly improved the ability to write poetry with a t-count value of 4.512 (p < 0.05). This suggests that the synectic model has a positive influence on poetry writing ability, suggesting that creative learning approaches can effectively improve students' writing skills and creativity